PEMAHAMAN DAN PELAKSANAAN NILAI-NILAI AKUNTANSI SYARIAH PADA PRAKTISI PEGADAIAN SYARIAH (STUDI KASUS PADA PT. PEGADAIAN SYARIAH SE-KABUPATEN TAPANULI BAGIAN SELATAN) - Windari, Windari (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2018)
This study aims to determine the understanding and implementation of Islamic accounting values in sharia pawnshop practitioners. Data sources used by all employees of PT. Pegadaian Syariah District of South Tapanuli with a total of 14 respondents. From the results of this study, it can be understood that the humanist value of the employer is very adequate, the under